2019
DOI: 10.1590/s1678-3921.pab2019.v54.00577
|View full text |Cite
|
Sign up to set email alerts
|

Productive performance and quantitative carcass traits of lambs fed saccharine sorghum silage

Abstract: The objective of this work was to evaluate the productive performance and carcass traits of lambs fed silages of different types of sorghum and corn. Thirty-two uncastrated male Suffolk lambs were used. The experimental design was completely randomized, with four treatments (silages) and eight replicates (animals). Silages of the GrandSilo forage sorghum, BRS 506 saccharine sorghum, BRS 511 saccharine sorghum, and the BRS 2223 double-grain corn hybrid were tested. The lambs fed sorghum silages had a lower dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Forage sorghum [Sorghum bicolor (L.) Moench] is a C 4 crop widely adapted to different environmental conditions, with high water use efficiency, forage yield, and a less demanding fertility than other agricultural crops (Híbrido BRS 655…, 2009;Borba et al, 2012;Cardoso et al, 2012;Qu et al, 2014;Barcelos et al, 2016;BRS 658…, 2016;Tolentino et al, 2016;Pino & Heinrichs 2017;Manarelli et al, 2019). Among the forage sorghum hybrids available in the market, 'BRS 655' and 'BRS 658' hybrids stand out for their productive stability, resistance to drought and high-quality forage, with high levels of protein and digestibility (Híbrido BRS 655…, 2009;BRS 658…, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Forage sorghum [Sorghum bicolor (L.) Moench] is a C 4 crop widely adapted to different environmental conditions, with high water use efficiency, forage yield, and a less demanding fertility than other agricultural crops (Híbrido BRS 655…, 2009;Borba et al, 2012;Cardoso et al, 2012;Qu et al, 2014;Barcelos et al, 2016;BRS 658…, 2016;Tolentino et al, 2016;Pino & Heinrichs 2017;Manarelli et al, 2019). Among the forage sorghum hybrids available in the market, 'BRS 655' and 'BRS 658' hybrids stand out for their productive stability, resistance to drought and high-quality forage, with high levels of protein and digestibility (Híbrido BRS 655…, 2009;BRS 658…, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Originating in Africa, sorghum is adapted to grow in arid and semi-arid environments (Hmielowski, 2017;Manarelli et al, 2019). As it is a plant with C4 metabolism, it has high photosynthetic capacity with great inherent potential for biomass production.…”
Section: Introductionmentioning
confidence: 99%
“…The diet of lambs can modify their carcass conformation and meat physical-chemical and organoleptic properties, such as fatty acid profile, softness and colour (Franco, Crecente, Vá zquez, Gómez, & Lorenzo, 2013). The silage offered to animals can affect the quality of their final products, such as milk and meat (Campos et al, 2017;Milewski et al, 2014), denoting the importance of studies that investigate the diet effects (Holanda Júnior, 2006;Manarelli et al, 2019;Pereira et al, 2016). Considering that other studies (Manarelli et al, 2019;Orrico Junior et al, 2015) found variations in the effect of 'BRS506' saccharin sorghum silage on animal performance and carcass characteristics, it is important to evaluate the quality parameters of meat of sheep fed with this silage.…”
Section: Introductionmentioning
confidence: 99%